Effectiveness and Safety of a Shorter Treatment Regimen in a Setting with a High Burden of Multidrug-Resistant Tuberculosis - Trubnikov, Aleksandr (Int J Environ Res Public Health, 2021)
Treatment of drug-resistant tuberculosis is lengthy, insufficiently effective, and toxic. Since 2016, the World Health Organization has recommended shorter treatment regimens (STR). We assessed effectiveness and predictors of drug adverse events (DAE) among patients treated with STR. There were 95 consecutive rifampicin-resistant patients enrolled in STR in Tashkent between June 2018 and September 2019. Of these, 66.3% were successfully treated, 17.9% suffered failed treatment, 7.4% died, 5.3% were lost to follow-up and 3.2% were not evaluated. No recurrence was identified in 54 patients after 12 months of successful treatment completion. There were 47 reported DAE: the incidence rate was 6.15 DAE per 100 person-months-of-treatment. Any DAE was reported in 38 (40%) patients and grade 3/4 DAE were recorded in 21 (22.1%) patients. Median time to DAE was 101 (interquartile range 64–139) days. The most frequently encountered DAE were gastro-intestinal disorders, followed by hepatotoxicity and ototoxicity. The most commonly offending drug inducing DAE was protionamide. The dose was temporarily interrupted in 55.3% of DAE, reduced in 8.5% of DAE and permanently withdrawn in another 8.5% of DAE. HIV status was the only predictor associated with increased hazard of DAE. In Uzbekistan STR showed moderate effectiveness and safety, although treatment failure was high.